The Effectiveness of Anti-Money Laundering /Counter Financing of Terrorism Requirements in Fund Management Companies/ Norziaton Ismail Khan ... [et al.] - Abdul Jani, Mohamad Asri; Zulkifli, Anis Asfarina; Ismail Khan, Norziaton (Universiti Teknologi MARA Cawangan Sarawak, 2021)
Anti-Money Laundering / Counter Financing of Terrorism (AML/CFT) broadly encompasses regulatory requirements, acts and guidelines designed to curtail the practice of generating funds through unlawful or criminal activities. Several infringement notices were issued to market intermediaries due to provision breaches of the guidelines. Although policies and procedures have been tightened up to the level of satisfaction, assessing the effectiveness of AML/CFT legislation is still necessary. The main aim of the study is to examine the independent variables, namely competency level of compliance team members, regulatory compliance and quality of AML/CFT framework that influence the effectiveness of AML/CFT requirements of the compliance officers that are working in FMCs in Malaysia. The Expectancy Theory has been applied to form the framework and to develop the hypotheses. Three hypotheses were developed and tested using the data from 70 samples of FMC's in Malaysia. The result of the study showed that there were significant relationships between the factors analysed in this study. This study will help the financial institutions especially the Fund Management Companies (FMCs) in understanding the factors that influence the effectiveness of AML/CFT requirements and taking necessary action to enhance their internal AML/CFT process and its compliance with the regulations. This would help the FMCs to have effective control of AML/CFT during the on-boarding and ongoing monitoring process.